Elevated monocyte-to-lymphocyte ratio, C-reactive protein and further inflammatory parameters as potential biomarkers of suicide risk in bipolar I disorder - Pethő, Borbála; Herold, Róbert; Simon, Diána; Kovács, Márton Áron; Tóth, Tünde; Albert, Noémi; Hebling, Dóra; Hajnal, András Sándor; Csulak, Tímea; Herold, Márton; Tényi, Tamás (Frontiers in Psychiatry, 2025)
Suicide is an unresolved issue in psychiatry to this day. Suicide risk (SR) is particularly high for psychiatric patients with bipolar I disorder (BD). Recent studies suggest an immunological dysregulation in the background. In our retrospective study, we investigated laboratory parameters of BD in-patients (n = 116) between January 2020 and June 2024. Data was collected regarding the following parameters: white blood cell, neutrophil, lymphocyte, monocyte and platelet count, monocyte-to-lymphocyte (MLR), neutrophil-to-lymphocyte (NLR) and platelet-to-lymphocyte ratio (PLR), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), red blood cell distribution width (RDW) and mean platelet volume (MPV). Individuals with recent (≤ 48 hours prior) suicide attempt (SA) (n = 21) and with past (> 48 hours prior) SA (n = 16) represented the high SR group (n = 37). BD patients with no history of SA composed the intermediate SR group (n = 79). We found a significant increase in MLR, monocyte count, CRP and ESR in patients with recent SA compared to those with no history of SA. Comparing high and intermediate SR patients, MLR, monocyte count, CRP and ESR remained elevated in the former group. As implied by previous research, immunological mechanisms may contribute to the emergence of suicidality. Investigating BD patients as the subgroup at significant risk, changes in certain inflammatory markers further strengthen the assumption of immunological processes in the background of suicidality, and these parameters may serve as potential future biomarkers of SR.